Optimasi Kombinasi Polietilen Glikol dan Polivinilpirolidon sebagai Bahan Pembawa pada Dispersi Padat Glibenklamid dengan Desain Faktorial (Optimization of Polyethilen Glycol and Polyvinylpirolidone Combination as the Carrier in Glibenclamide Solid Disp - Hendra Kurniawan; Budipratiwi Wisudyaningsih; Dwi Nurrahmanto (Pustaka Kesehatan, 2016)
Glibenclamide is a second-generation sulfonylurea which indicated for the treatment of type II diabetes mellitus. Glibenclamide included in class II of BCS, a drug that have a good permeability but low in solubility. One of techniques that can be used to increase the solubility of glibenclamide is solid dispersion technique. This study was aimed to determine the effect of PEG 6000 and PVP K-30 combination on the melting point of solid dispersion, release of glibenclamide in solid dispersion and the optimum composition of their combination with factorial design method. Melting point response tested using melting point apparatus and percent release response tested by in vitro dissolution test. The results showed that increasing PEG 6000 and PVP K-30 will decrease melting point response and increase percent release response. The optimum composition of those combination was 700 mg of PEG 6000 and 1000 mg of PVP K-30 which provided the smallest melting point at 159,333oC and greatest release as 97.9067%. The optimum composition was characterized using FTIR, DSC and SEM. Keywords: glibenclamide, PEG 6000, PVP K-30, solid dispersion, factorial design